PENGEMBANGAN MODEL PEMBELAJARAN PAI BERBASIS PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN CRITICAL THINKING SISWA - Moh Mundzir (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2026)
This study aims to: (1) analyze the effectiveness of the Problem-Based Learning (PBL) model in improving students’ critical thinking skills in Islamic Religious Education (PAI), and (2) examine the relevance of PBL implementation to the characteristics of PAI learning and the demands of 21st-century education. This research employs a Research and Development (RD) approach, consisting of needs analysis, model design, product development, expert validation, field testing, and revision stages. Data collection techniques include observation, interviews, questionnaires, and critical thinking tests, which are analyzed using both descriptive and quantitative methods. The results of the study indicate that the implementation of the PBL model is effective in enhancing students’ critical thinking skills, as evidenced by improvements in analysis, evaluation, and rational decision-making abilities. Furthermore, the PBL model is proven to be relevant to PAI learning as it integrates cognitive, affective, and psychomotor aspects through active, collaborative, and contextual problem-based learning. Therefore, PBL is considered an appropriate learning model to address the challenges of 21st-century education and to improve the overall quality of Islamic Religious Education. ABSTRAKPenelitian ini bertujuan untuk: (1) menganalisis efektivitas model pembelajaran problem based learning (PBL) dalam meningkatkan kemampuan berpikir kritis siswa pada mata pelajaran Pendidikan Agama Islam (PAI), serta (2) mengkaji relevansi penerapan PBL dengan karakteristik pembelajaran PAI dan tuntutan pendidikan abad ke-21. Penelitian ini menggunakan pendekatan research and development (RD) dengan tahapan analisis kebutuhan, perancangan model, pengembangan produk, validasi ahli, uji coba, dan revisi. Teknik pengumpulan data meliputi observasi, wawancara, angket, dan tes kemampuan berpikir kritis, yang dianalisis secara deskriptif dan kuantitatif. Hasil penelitian menunjukkan bahwa penerapan model PBL efektif dalam meningkatkan kemampuan berpikir kritis siswa, yang ditandai dengan meningkatnya kemampuan analisis, evaluasi, dan pengambilan keputusan secara rasional. Selain itu, model PBL juga terbukti relevan dengan pembelajaran PAI karena mampu mengintegrasikan aspek kognitif, afektif, dan psikomotorik melalui pembelajaran aktif, kolaboratif, dan berbasis masalah kontekstual. Dengan demikian, PBL menjadi salah satu model pembelajaran yang sesuai untuk menjawab tantangan pendidikan abad ke-21 serta meningkatkan kualitas pembelajaran PAI secara menyeluruh.